2017
DOI: 10.1186/s12864-017-3848-6
|View full text |Cite
|
Sign up to set email alerts
|

The biocontrol agent Pseudomonas chlororaphis PA23 primes Brassica napus defenses through distinct gene networks

Abstract: BackgroundThe biological control agent Pseudomonas chlororaphis PA23 is capable of protecting Brassica napus (canola) from the necrotrophic fungus Sclerotinia sclerotiorum via direct antagonism. While we have elucidated bacterial genes and gene products responsible biocontrol, little is known about how the host plant responds to bacterial priming on the leaf surface, including global changes in gene activity in the presence and absence of S. sclerotiorum.ResultsApplication of PA23 to the aerial surfaces of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 76 publications
1
27
0
2
Order By: Relevance
“…In addition to direct growth antagonism of microbes, the phenazines also induce systemic resistance in plants such that protection against shoot pathogens is triggered by root colonization with P. chlororaphis isolates. Both PCN-and PCA/2-OH PHZ-producing microbes possess this ability [23][24][25]. Duke et al [23] observed that aerial application of isolates induces both localized and systemic responses associated with resistance.…”
Section: Beneficial Traits Of P Chlororaphis Isolates In the Rhizospmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to direct growth antagonism of microbes, the phenazines also induce systemic resistance in plants such that protection against shoot pathogens is triggered by root colonization with P. chlororaphis isolates. Both PCN-and PCA/2-OH PHZ-producing microbes possess this ability [23][24][25]. Duke et al [23] observed that aerial application of isolates induces both localized and systemic responses associated with resistance.…”
Section: Beneficial Traits Of P Chlororaphis Isolates In the Rhizospmentioning
confidence: 99%
“…Both PCN-and PCA/2-OH PHZ-producing microbes possess this ability [23][24][25]. Duke et al [23] observed that aerial application of isolates induces both localized and systemic responses associated with resistance. Thus, the direct microbial antagonism caused by phenazine production is reinforced by the phenazinemediated upregulation of plant defence mechanisms.…”
Section: Beneficial Traits Of P Chlororaphis Isolates In the Rhizospmentioning
confidence: 99%
“…chlororaphis, can function as biocontrol agents to directly inhibit the growth of fungal, bacterial, and eukaryotic pathogens through the action of secreted compounds [12][13][14][15][16]. P. chlororaphis strain PA23, a microbe originally isolated from the soybean rhizosphere, is a potent biocontrol agent against fungal pathogens and parasitic nematodes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Phyllosphere, also known as aerial part of plant, is the first-line plants used to fight against pathogen infections (Berg, 2009;Natacha et al, 2014). Phyllosphere also provides an ideal habitat for bacterial species that are beneficial to plant growth and stress tolerance (Vorholt, 2012;Kembel et al, 2014;Duke et al, 2017). Successful applications of microbes with biocontrol activities to plant phyllosphere are crucial for effective crop disease managements (Kim et al, 2011;Lambais et al, 2014).…”
Section: Introductionmentioning
confidence: 99%